A Novel Decentralized and Flexible Policy for Flow Mobility Management - Pastori, Edivaldo [UNESP]; Guidoni, Daniel L.; Villas, Leandro Aparecido; De Grande, Robson E.; Meneguette, Rodolfo (Institute of Electrical and Electronics Engineers (IEEE), 2020)
Intelligent Transport Systems rely extensively on the proper management of vehicular resources, as well as the underlying vehicular communication. Services and applications are made accessible through the communication of vehicles, which is expected to happen without any interruption; however, the high mobility of vehicles is detrimental towards their connectivity and communication stability. In this highly dynamic and heterogeneous vehicular scenario, we assume the existence of multiple communication interfaces and high movement speed of nodes. Thus, we propose the development of a flow mobility management policy. The policy is devised following a decentralized design, being flexible and capable of providing transparent flow management to users while maintaining continuous service access. We conducted experimental simulations for evaluating the proposed architecture, as well as making performance comparisons with three related flow management works. The results showed that the proposed policy reduces the delay of information exchange to approximately 50 ms, decreases handover time (0.5s), and maximizes the input of information around 95%.